Medicare and the geography of financial health - Paul Goldsmith-Pinkham; Maxim Pinkovskiy; Jacob Wallace (Federal Reserve Bank of New York, 2020)
We use a five percent sample of Americans' credit bureau data to study the effects of public health insurance on the geography of consumer financial health. Exploiting the nearly universal eligibility for Medicare at age 65, we find a 30 percent reduction in the level of debts in collections with limited effects on other financial outcomes. Medicare reduces the geographic variation in collections by two-thirds at age 65 and halves the geographic correlation between collections and demographics like race and education. Areas that experienced the largest gains in financial health at age 65 had higher shares of black residents, people with disabilities, and for-profit hospitals.
Keywords: G51; G52; I13; 330; Medicare; household finance; heterogeneity